Engaging With The Past: A history of public history on the island of Ireland in the state formation period, and an investigation into the effects of public historical engagement. - White, Caitlin Ann (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2023)
This thesis investigates the role of public history, in the form of monumental memorials, in shaping identity narratives during the state-formation period in Ireland and Northern Ireland. By employing an all-island approach encompassing both urban capital cities and smaller rural towns, this research explores the diverse strategies used to promote identity narratives in four case study areas. Comparative analysis in Chapters 1-3 examines these case studies on an all-island basis, highlighting developments in capital cities and local communities. By exploring the historical context and spatial dynamics of monumental memorials, this research offers insights into the utilisation of public history and the identities being promoted in the public space. Innovative methodologies drawn from sociology and pedagogy are employed alongside traditional research methods to create public history workshops, the process and results of which are documented in this thesis. Chapter 4 describes the creation of workshops based on local history case studies, serving as a transformative element that bridges academia and public engagement. Implemented in Nenagh and Dublin, these workshops yield invaluable data for the field of public history, enriching the understanding of history's impact on individuals and communities. Findings indicate that active participation in public history enhances critical thinking, promotes multiperspectivity, nurtures empathy, and fosters a connection to local historical heritage. These outcomes underscore the significance of public history in society. By examining the interplay between monumental memorials, identity narratives, and public engagement with history, this thesis contributes to the field of public history. It offers valuable insights for policymakers, historians, and educators seeking inclusive and reflective approaches to the construction of the past.
APPROVED
Keywords: workshops; public engagement; critical thinking; multiperspectivity; identity narratives; memory; public history; monumental memorials; monuments; First World War; Irish Revolution; Irish Civil War; Irish War of Independence; 1916 Rising; commemoration; Ireland; Northern Ireland; twentieth century; comparative study; case studies; urban capital cities; rural towns; empathy; collective memory; social memory.